Automated determination of active compounds in pharmaceutical formulations by flow injection analysis - Kukoč Modun, Lea (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Presents automated flow injection analysis methods for thiol compound quantification in pharmaceuticals. Discusses kinetic analysis principles, selectivity based on reaction mechanisms, and advantages for pharmaceutical quality control.